The Contemporary Family in France : Partnership Trajectories and Domestic Organization - Régnier-Loilier, Arnaud (INED Population Studies, 2015)
This book provides a portrait of the family in France today, revealing many of the deep-seated, demographic changes that have affected French society in recent decades. It first focuses on conjugal and family trajectories, examining union formation, types of union, entry into parenthood, influence of religion, and separation. Next, the book explores domestic organization within the couple. It looks at gender differences in attitudes to task-sharing, division of household and parenting tasks, influence of past partnership history, and changes after a birth. The book presents a series of studies based on the French version of the international Generations and Gender Survey, a major comparative research project conducted in 20 countries to collect information from individuals aged 18-79 about relationships and processes in the life course. Inside, readers will find insightful analysis of the survey results by sociologists, demographers, and economists, and come to better understand recent demographic and social developments in France as well as the factors influencing them. The book will appeal to a broad audience of students and researchers interested in family, gender, and intergenerational relations. In addition, as the survey data are comparable across countries, the book will provide researchers with ideas for further research opportunities in Europe and beyond.